Reaction of huisgen zwitterion with diaryl-1,2-diones and ketones: an efficient protocol for carbon-nitrogen bond formation - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C. (Synthesis-Stuttgart, 2007)
The reaction of Huisgen zwitterion, derived from triphenylphosphine and dialkyl azodicarboxylate, with diaryl-1,2-diones afforded N,N-dicarboalkoxy monohydrazones via a mechanistically novel rearrangement. Cyclic and acyclic ketones furnished vinyl hydrazinedicarboxylates under similar conditions.
Keywords: betaines - diazo compounds - hydrazones - ketones - rearrangements

Reaction of tpp-azodicarboxylate zwitterions and aldehydes: unprecedented synthesis of acyl carbamates - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Tetrahedron Letters, 2007)
An efficient synthesis of acyl carbamates from aryl aldehydes by the reaction of triphenylphosphine and dialkyl azoesters is described.

Reaction of huisgen zwitterion with diaryl ketones leading to the facile synthesis of mono- and bis(alkoxycarbonyl)hydrazones - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2008)
The Huisgen zwitterion, generated from triphenylphosphine and dialkyl azodicarboxylates, afforded upon reaction with diaryl ketones both mono- and bis(alkoxycarbonyl)hydrazones, depending on the reaction conditions.

Reactions of morita-baylis-hillman acetates with huisgen zwitterions: a novel strategy for the synthesis of ?-amino acid derivatives - Jose, Anu; Paul, Rony Rajan; Mohan, Resmi; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh; Nair, Vijay (Synthesis, 2009)
The reaction of Huisgen Zwitterion with Morita–Baylis– Hillman acetates afforded b-amino acid derivatives.
Keywords: b-amino acid; Huisgen zwitterion; Morita–Baylis–Hillman acetate